Recent Advancements in System Modelling Applications Proceedings of National Systems Conference 2012 - Malathi, R.; Krishnan, J.; SpringerLink (Online service) (India : Springer India : Imprint: Springer, 2013)
The book is a collection of peer-reviewed scientific papers submitted by active researchers in the 36th National System Conference (NSC 2012). NSC is an annual event of the Systems Society of India (SSI), primarily oriented to strengthen the systems movement and its applications for the welfare of humanity. A galaxy of academicians, professionals, scientists, statesman and researchers from different parts of the country and abroad are invited to attend the Conference. The book presents various research articles in the area of system modelling in all disciplines of engineering sciences as well as socio-economic systems. The book can be used as a tool for further research.
Preface -- Table of Contents -- About the Editors -- Papers -- Author Index.
Keywords: Engineering; Systems theory; Computer engineering; Engineering; Computational Intelligence; Systems Theory, Control; Electrical Engineering